Effects of ricin on primary pulmonary alveolar macrophages. Issue 8 (August 2019) - Guo, Zhendong; Wang, Zhongyi; Meng, Shanyu; Zhao, Zongzheng; Zhang, Chunmao; Fu, Yingying; Li, Jiaming; Nie, Xin; Zhang, Cheng; Liu, Linna; Lu, Bing; Qian, Jun
Objective: We systematically investigated the cytotoxic effects of ricin in primary pulmonary alveolar macrophages (PAMs). Methods: Primary PAMs were isolated from BALB/c mice. The cytotoxic effects of ricin were investigated in vitro by optical and transmission electron microscopy, detection of the inflammatory cytokine response, proteomic analysis, and subsequent biological functional analysis. Results: Ricin induced shrinkage, apoptosis, vacuolization, and multi-organelle lesions in primary PAMs as demonstrated by optical and transmission electron microscopy. Ricin also induced a pronounced pro-inflammatory cytokine response in primary PAMs, including induction of tumor necrosis factor-α, interferon-γ, interleukin (IL)-1, IL-2, IL-6, IL-12, C-C motif chemokine ligand 2, and C-X-C motif chemokine ligand 2, while the anti-inflammatory cytokines IL-4 and IL-10 were less affected. Proteomic analysis and subsequent biological functional analysis identified eight proteins that were up/downregulated by ricin treatment and which might thus contribute to ricin toxicity. These proteins were involved in various functions, including redox, molecular chaperone, glycolysis, protein translation, and protein degradation functions. Conclusion: The results of the present study further our understanding of the pathogenic mechanism of inhalational ricin poisoning.